Viral Diarrhoea in Children of Dhulikhel Hospital, Nepal and Medical University of Innsbruck, Austria - Joshi, Anish; Shrestha, Ranendra Prakash Bahadur (Annals of Clinical Chemistry and Laboratory Medicine, 2016)
BACKGROUND Viral diarrhoea is still a major cause of childhood morbidity and mortality worldwide, with high morbidity in children younger than 5 years of age particularly in developing countries. The objective of this study was to determine the frequency of viral diarrhoea in children less than 5 years of age at Kathmandu University Hospital/Dhulikhel Hospital (DH), Nepal and Medical University of Innsbruck (MUI), Austria and to compare the clinical presentation and the common cause of acute childhood diarrhoea in the two institutions. METHODS This was a hospital based, comparative study done in two different hospitals DH and MUI. A total of 200 cases of under 5 years old children, among which 100 cases attending DH from 1st December 2011 to 29th February 2012 and 100 cases attending MUI from 1st March 2012 to 31st May 2012, presented with acute onset of diarrhoea were enrolled in the study. The fresh stool specimens were analysed in the laboratory of individual hospital in order to examine the common pathogens. RESULTS Majority of children were classified as no dehydration (DH: 75% and MUI: 74%); in DH 5% were classified as severe dehydration, whereas in MUI it was null. In MUI, 96% of children were brought within 3 days of illness, whereas only 32% were brought in DH which was statistically significant (p=<0.001). In DH 37% of cases required hospital admission, among which 7 cases needed PICU, whereas in MUI, 52% of cases were admitted (p=0.03); and no cases needed PICU. The mean hospital stay was 1.1±1.7 days and 1.3±1.8 days in DH and MUI, respectively. Rotavirus was positive in significant number of cases in DH (66%) (p=<0.001). Other pathogen detected in DH was Adenovirus (13%). The most common pathogen detected in MUI was Norovirus (16%), followed by Rotavirus (11%) and Adenovirus (9%). CONCLUSIONS Incidence of acute diarrhoea was highest below 24 months of age. Rotavirus and Norovirus was the most common cause of children diarrhoea in Nepal and Austria, respectively.